P430 Predictors of interest in switching from daily to on-demand HIV Pre-Exposure Prophylaxis (PrEP) among australians. (14th July 2019) - Cornelisse, Vincent; Lal, Luxi; Price, Brian; Wright, Edwina
Abstract : Background: The only HIV pre-exposure prophylaxis (PrEP) regimen approved in Australia is daily co-formulated tenofovir and emtricitabine. As an alternative, on-demand PrEP could offer benefits, including lower pill burden for people having sex infrequently. We surveyed PrEPX study participants to measure interest in switching from daily PrEP to on-demand PrEP. Methods: The survey asked 15 questions on demographics, sexual behaviour, interest in on-demand PrEP, and reasons for interest. Univariate regression analyses assessed associations between interest in on-demand PrEP and other survey questions, and questions with significant (p<0.1) association in univariate analysis were entered in a multivariate regression model. Results: 970 responses were complete. Respondents' median age was 39 years, and 99.6% were male. All had taken daily PrEP, but 14% had ceased PrEP. 469 respondents (48%; 95%CI 45–52) reported interest in on-demand PrEP. In multivariate analysis, interest in on-demand PrEP was independently associated with having ceased PrEP (aOR 2.0, p<0.001), dissatisfaction with daily PrEP (aOR 2.0, p=0.027), difficulty remembering to take pills every day (aOR 1.6, p=0.029), infrequently having sex that conferred HIV risk (aOR 3.7, p<0.001), concerns about long term toxicity from PrEP (aOR 2.7, p<0.001), and having no prior knowledge of on-demand PrEP (aOR 1.6, p<0.004). Respondents who were not interested in on-demand PrEP (N=501) reported concerns about its effectiveness (67%), concerns about not remembering to take a dose at least 2 hours before sex (58%), having unplanned sex (15%), and having frequent sex and hence needing to take PrEP daily (2%). Conclusion: This is the first study of interest in switching from daily to on-demand PrEP. Half of respondents were interested, and interest was most strongly associated with infrequency of sex and concerns about long-term toxicity. However, many respondents had concerns about the effectiveness of on-demand PrEP, and about forgetting to take on-demand PrEP at least two hours before sex. Disclosure: No significant relationships.